ChemInform Abstract: First Palladium‐Catalyzed Direct Regioselective C‐5 (Het)Arylation of Mono‐ or Disubstituted Thiazolo[3, 2‐b][1, 2, 4]triazoles. Issue 7 (29th January 2015) - Le Meur, Mikael; Bourg, Stephane; Massip, Stephane; Marchivie, Mathieu; Jarry, Christian; Guillaumet, Gerald; Routier, Sylvain
Abstract A reaction sequence involving formation of thiazolo[3, 2‐b]triazoles followed by efficient directed C‐H activation in the presence of a Pd‐catalyst to synthesize di‐ and trisubstituted derivatives with full regioselectivity is presented.